Stonewall 50 published in conjunction with an exhibition held at Contemporary Arts Museum Houston, April 27 - July 28, 2019 (Contemporary Arts Museum Houston, 2019)
Stonewall 50' is an exhibition conceived as a snapshot of the complexion, interests, and activities of a diverse group of queer and allied artists. Whether working in local communities or on other continents, these artists? responses to the worlds around them?in photographs, paintings, films and videos, sculptures, performances, and other media?address a range of personal and collective concerns and desires. Stonewall 50 follows a number of paths: it traces artists? engagement with trans visibility; suggests possibilities for formal and conceptual inter-generational dialogue; and looks outside the United States to consider queer issues abroad. While these themes provide a framework for the exhibition, the show?s contents are not limited to artworks exploring these notions. This exhibition is organized with an understanding that the privileges and disadvantages that affect the self-determination of sex and gender expression are linked inextricably to cultural perceptions around ability, age, nationality, race, wealth, and a host of other issues.00Exhibition: Contemporary Arts Museum, Houston, USA (27.04.-28.07.2019)